Facial nerve palsy in the course of herpes zoster infection – challenges in the treatment and prognosis - Pietrzak, Maja; Śpiewak-Pokorska, Maria; Pluta, Magdalena; Marczyńska, Magdalena (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Facial nerve palsy occurs in paediatric population with the incidence of 4.2-15.3/100 000. In most cases etiology remains unknown (Bell’s palsy – idiopathic facial nerve palsy). Infectious agents account for around 25% of cases. This paper describes 2 cases of facial nerve palsy due to herpes zoster infection: a 9-year-old girl with vesicular lesions on the right side of the neck and face with concomitant right sided facial nerve palsy, and a 16-year-old boy* with lesions located in the left external auditory meatus who developed Ramsay-Hunt syndrome. The course of the disease and response to treatment in both patients was significantly different.